PENINGKATAN KINERJA BISNIS USAHA KECIL DAN MENENGAH DENGAN STRATEGI HARGA, PENERAPAN TEKNOLOGI DAN KEWIRAUSAHAAN - R.Ferry Bakti Atmaja; Seno Hadi Saputro; R. Burham Isnanto; Ari Amir Alkodri (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
Abstrac : The role of MSMEs in many developing countries such as Indonesia has difficulty in increasing their output because they are unable to compete with online stores. Pricing strategy is a way to maintain the liquidity of a company. Utilization of Information Technology in MSMEs is needed considering the low utilization of Information Technology caused by low understanding of the benefits of Information Technology. Marketing strategies must be applied to small and medium-sized businesses so that their trade turnover remains stable with innovations and new breakthroughs being carried out. The purpose of this study was to determine the effect of pricing strategies, application of technology, and entrepreneurial ability on MSME business performance. The research method was conducted by distributing questionnaires to 110 respondents and using 4 hypotheses. Several tests were conducted including validity test, reliability test, nromality test, multicollinearity test, heteroscedasticity test, coefficient of determination Test, T test and F test. The final result of the study is from the coefficient of determination test has an adjusted R square of 0.602 means that 60.2% of the three variables can explain the variance of business performance variables, for the remaining 39.8% explained other variables. From the calculation of F obtained F count value 56,000 greater than F table 2.69 means that the variable price strategy, application of technology, and entrepreneurial ability have a simultaneous effect on business performance